Iure Theutonico? German settlers and legal frameworks for immigration to Hungary in an East-Central European perspective. Issue 3 (27th May 2019) - Szende, Katalin
ABSTRACT: The article discusses the strongly disputed and over-politicised presence of the Germans, the single most populous minority ethnic group in medieval East-Central Europe, and their impact on their host societies, notably the kingdoms of Hungary, Poland and Bohemia, and the duchy of Silesia. It examines the routes and reasons for the arrival of the immigrant population, the topography of settlement and the activities pursued; and it discusses the legal background to the arrival of immigrants and their co-existence with the majority society. In most of East-Central Europe, the arrival of the German settlers led to the adaptation of ius Theutonicum, a framework created by sovereigns to accommodate the immunities and obligations of the newcomers. In Hungary, it never took root. Instead, settlers were accommodated legally by means of the liberties of hospites, until this stratum of external and internal migrants was absorbed into peasantry and bourgeoisie, respectively.